Face Capture-Based Employee Attendance System: A Case Study of Holy Innocents Children’s Hospital Mbarara - Innocent Byarugaba (Uganda Christian University, 2024)
The Research will be conducted on 5th March 2024 at Holy Innocents Childrens’ Hospital located on Plot 6, Nyamitanga ward,Nyamitanga Division, Mbarara city South, Mbarara City, Uganda. It is 3kms (2mls) from Mbarara Regional Referral Hospital on the high way Kaberebere Isingiro Road on the left-hand side. It is a pediatric general hospital in the western region of Uganda founded in 2009, and it is the second pediatric hospital in Uganda after Cure Children’s Hospital of Uganda (CCHU) in Mbale Eastern Uganda which was founded in 2000. This document of the research proposal is for developing a Face capture-based employee attendance system for Holy Innocents Children’s Hospital. It consists of the current background of the Hospital and problems having due to present a system and how I will overcome those matters through my proposed system. After gathering the required information, I found HICH has no computerized system, they use manual system where people could go directly and register their attendance in the register book or counter books, and then the information is stored in the counter books. Staffs sign for their friends as if they have attended to work. This have made patients not being attended to and some turn back home with their sickness and others to the neighborhood hospitals due to absenteeism. For the case of HICH is a business oriented, this puts the hospital and its Directors at a stake of losing business. The research project is aimed at designing a fully functional Face capture-based employee attendance system in order to manage absenteeism. The overall mission of system development is to make Hospital Director easily and quickly track staff attendances.